Elastic And Dynamic Response Characteristics Of Kenaf/polypropylene Composites - Anwar, P. P. A. Majeed; David, N. V.; S., Khairiyah (WIT Press, 2012)
The elastic and dynamic characteristics of natural fibre based materials are of particular concern for packaging applications. In this study, the tensile and flexural behaviour of kenaf filled polypropylene (kenaf/PP) composites are experimentally studied. The mass fraction of kenaf is varied from 0wt% to 60wt% in 10% increments. Two rates of extensions, namely, 2mm/min and 10mm/min are used for the tensile test. The flexural test is conducted at a rate of 1mm/min with reference to the ASTM D790-10 standard. The results obtained indicate that the elastic modulus of the kenaf/PP composites increases while the Ultimate Tensile Stress (UTS) of the composites decreases with increasing fibre loadings. It is found that the elastic modulus of the 60wt% composite increases from 1.89GPa to 2.64GPa when the extension rate is increased from 2mm/min to 10mm/min. For this same increment of extension rate, it is observed that the UTS of the composites reduces when the fibre loadings are increased with the 10mm/min rate registering higher UTS values than that by the 2mm/min rate. The stiffness of the composites in tension thus increases at the expense of their strength when the extension rate is increased. A semi-empirical model employed in this study also predicts similar responses. The stiffness of the composites in bending mode is found to be little affected by the fibre content in the neat PP. The fracture toughness of the kenaf/PP composites decreases by 56% as the fibre fraction is increased from 10wt% to 60wt%. The first three modes of vibration of the composites are simulated using ANSYS® ver. 12.1 program. The natural frequencies corresponding to the elastic response of the composites at the two extension rates for these modes fluctuate between 208Hz and 725Hz. Keywords: kenaf, agro-waste, bio-composites, tensile properties, dynamic characteristics, empirical models.